Aortic valve replacement through minithoracotomy. Results from the Peruvian experience - Ríos-Ortega, Josías C. (2022)
Objectives. To assess mortality, major valve-related events (MAVRE), and other complications in the perioperative period and follow up in patients with aortic valve replacement (AVR) through minithoracotomy (MT). Methods. We retrospectively analyzed patients aged <80 who underwent AVR through MT between January 2017 and December 2021 in a national reference center in Lima, Peru. Patients undergoing other surgical approaches (mini-sternotomy, etc.), other concomitant cardiac procedures, redo, and emergency surgeries were excluded. We measured the variables (MAVRE, mortality, and other clinical variables) at 30 days and a mean follow-up of 12 months. Results. Fifty-four patients were studied, the median age was 69.5 years, and 65% were women. Aortic valve (AV) stenosis was the main indication for surgery (65%), and bicuspid AV represented 55.6% of cases. At 30-days, MAVRE occurred in two patients (3.7%), with no in-hospital mortality. One patient had an intraoperative ischemic stroke, and one required a permanent pacemaker. No patient underwent reoperation due to prosthesis dysfunction or endocarditis. In a mean follow-up of one year, MAVRE occurrence did not show variations with the perioperative period, most patients remained in NYHA I (90.7%) or II (7.4%) compared to the preoperative period (p<0.001). Conclusions. AV replacement through MT is a safe procedure in our center for patients under 80 years.